67/8-(-121/3)=

Simple and best practice solution for 67/8-(-121/3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67/8-(-121/3)= equation:


67/8-(-121/3)=0

We simplify the equation to the form, which is simple to understand
67/8-(-121/3)=0

Simplifying:
+8.375-(-121/3)=0

Simplifying:
+8.375-(-40.3333333333)=0

Remove unnecessary parentheses
+8.375+40.3333333333=0

We move all terms containing to the left and all other terms to the right.
0=0-8.375-40.3333333333

We simplify left and right side of the equation.
0=-48.7083333333

0=-48.7083333333

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 4x^2+10x+25=41 | | X^2+100x=9600 | | 23a-25a=2a | | 9x+1=x+6 | | 2(x-5)+4=10 | | 3x^2+5x-13=12 | | 14/25x15/52x8/21 | | -14h=13h-17 | | 3(h)=6 | | 1/2(16-2h)=11 | | 18-(-21)= | | 3x+4x-16+11=23 | | 2-4q=2+5q | | x/-4=-12 | | 2y-4=1 | | x+4+6=26-3x | | 1/4+1/4h=4 | | 2+9t=8t+7 | | 23=2y-13 | | 4x-2(x+5)=6 | | 24-3n-7=20 | | 6/5*(-10*8) | | x^2-8x+12=(x-2) | | 8x-3x+3=x-6+9 | | 210+500=s | | 9x+x-7=13 | | -12-10j=-9j | | .5x+.09x=251 | | 2(m-6)=-18 | | -26.17-(+18.52)= | | P=2(68)+2(145) | | -12(x-1)=4(x+13) |

Equations solver categories